Understanding the Nuclear Landscape in Southern Asia: Complexities and Possibilities. Issue 2 (3rd July 2022) - Sethi, Manpreet
ABSTRACT: The nuclear playground in Southern Asia is marked by an exceptional level of complexity. A number of players; their disparate thinking on how to establish deterrence; nuclear dyads that elongate into strategic chains; inter-twining of nuclear issues with conventional, space, cyber realms; disparities in military capabilities; historical animosities accentuated by unresolved territorial conflicts; divides that spawn ideologies, religions and civilizational issues; all make for an immensely complex situation. The consequent regional nuclear dynamics has fair potential for crisis and arms race instability. As a way to address the regional nuclear challenges, the paper explores the character of Pakistan–India and China–India nuclear dyads along three specific axes: drivers of conflict; points of commonalities, similarities and differences; and implications of these for their nuclear stockpiles. Armed with this understanding, it then offers some policy recommendations to address the concomitant dangers.